Analisis Pengaruh Debt To Equity (DER) dan Growth Opportunity Terhadap Nilai Perusahaan Pada PT. HM Sampoerna, Tbk - Azis, Andi; Munandar, Aris; Nurulrahmatiah, Nafisah (Pusat Riset dan Inovasi Nasional, 2026)
This research aims to analyze the influence of Debt to Equity Ratio (DER) and Growth Opportunity on the value of the company at PT HM Sampoerna Tbk. The research method used is quantitative with an associative approach, using financial statement data for the 2014–2023 period taken from the Indonesia Stock Exchange. The independent variables tested are DER and Growth Opportunity, while the dependent variable is the company value measured by Price to Book Value (PBV). Data analysis is carried out using classical assumption tests, multiple linear regression, correlation and determination coefficients, as well as t tests and F tests with the help of SPSS 26. The research results show that DER partially does not have a significant effect on the company's value (p = 0,315 > 0,05), while Growth Opportunity has a significant positive effect (p = 0,011 < 0,05). Simultaneously, DER and Growth Opportunity have a significant effect on the company's value (p = 0.0000 < 0.05) with a contribution of 54.9%, while the rest is influenced by other variables outside the model. This finding indicates that growth opportunities are the main factor considered by investors in increasing the value of the company, while the ratio of debt to equity is not the main focus in making investment decisions at PT HM Sampoerna Tbk.